Analysis of Islamic Banking Market Structure in Indonesia with Panzar-Rosse Model Approach - Kiki Hardiansyah Siregar; Ahmad Qarib; Dede Ruslan (Budapest International Research and Critics University, 2019)
The purpose in this study is to determine and analyze the market structure of the Islamic banking industry in Indonesia according to the Panzar-Rosse model and the level of competition between Islamic banking industry in Indonesia. To find out the market structure of the islamic banking industry it must be analyzed the effect of EAR, NPF, BOPO, FAR, FS, PL, PFF, PCE on the performance of Islamic banking as measured by ROA. The data used to answer and achieve these objectives is used secondary data from Islamic banks in Indonesia which has the largest asset ratings for a period of 6 years using the selected panel data method on the basis of Tests. The analysis model related to market structure uses the Panzar-Rosse model by looking for the H-statistic value and identified the Islamic banking equilibrium test on the panel data model of the performance of bank in Indonesia. This study found that the performance of Islamic banking measured by ROA simultaneously affected EAR, NPF, BOPO, FAR and FS and Panzar-Rosse approach will produce H-Stat value which is the sum of three main coefficients ofbanking inputs (labor, capital and funds). With H-Stat valued at 0.735 can be concludedthat the islamic banking industry in indonesia into the category of monopolistic market.The levels of the Islamic banking industry of Bank BNI, Bank BRI, Bank Panin and Bank Bukopin are monopolistic market while Bank Muamalat and Bank Mandiri are directed towards a joint monopoly market in the position of long-term equilibrium.